2014
DOI: 10.1063/1.4895568
|View full text |Cite
|
Sign up to set email alerts
|

Migration and vascular lumen formation of endothelial cells in cancer cell spheroids of various sizes

Abstract: We developed a microfluidic device to culture cellular spheroids of controlled sizes and suitable for live cell imaging by selective plane illumination microscopy (SPIM). We cocultured human umbilical vein endothelial cells (HUVECs) within the spheroids formed by hepatocellular carcinoma cells, and studied the distributions of the HUVECs over time. We observed that the migration of HUVECs depended on the size of spheroids. In the spheroids of $200 lm diameters, HUVECs migrated outwards to the edges within 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Reproduced from Ref. ( ) with permission from AIP Publishing LLC. C : Agarose container containing the 3D cell‐collagen mix for the TC‐LSFM set up.…”
Section: Parallelized Approaches To Increase Lsfm Throughputmentioning
confidence: 99%
“…Reproduced from Ref. ( ) with permission from AIP Publishing LLC. C : Agarose container containing the 3D cell‐collagen mix for the TC‐LSFM set up.…”
Section: Parallelized Approaches To Increase Lsfm Throughputmentioning
confidence: 99%
“…These combined effects offer a technique that allows the user to minimize both photobleaching and phototoxicity [10,[12][13][14], while allowing for long-term imaging studies (up to several days). This is an essential characteristic required for all sorts of developmental biology studies [15][16][17][18], such as organogenesis [19], cell migration [20,21], cardiac development [22][23][24][25], vascular development [26,27], neuro-development [28,29], and generally any kind of in vivo studies. Drosophila melanogaster [2,[30][31][32] and zebrafish [19,26,30,[33][34][35][36] have traditionally been the most widely used samples in this field, but it fits well many others, such as worm embryos [28,37] and other small organisms or plants [38][39][40].…”
Section: 1a Lsfm Is Low Photodamage and Low Phototoxicmentioning
confidence: 99%
“…9(a) and by using Eq. (27), it is possible to calculate the 3D LS intensity distribution and the overall PSF/MTF of the LSFM.…”
Section: 3a Linear Regimementioning
confidence: 99%
See 1 more Smart Citation
“…Patra et al reported migration and vascular lumen formation of cancer cell spheroids. 11 This group combined microfluidic devices and selective plane illumination microscopy (SPIM), which gives high resolution in both spatial and temporal domain. The observation of endothelial cells in spheroids provides insight on tumor vascularization, an ideal disease model for drug screening and fundamental studies.…”
mentioning
confidence: 99%